Don't Cross the Line: Bounding the Causal Effect of Hypergamy Violation on Domestic Violence in India - Punarjit Roychowdhury; Gaurav Dhamija (Global Labor Organization (GLO), 2022)
We empirically examine whether violation of hypergamy - which occurs when the wife's economic status equals or exceeds that of her husband's - causally affects domestic violence using microdata from India. Identifying the causal effect of hypergamy violation on domestic violence, however, is challenging due to unmeasured confounding and reverse causality. To overcome these difficulties, we utilize a nonparametric bounds approach. Relying on fairly weak assumptions, we find strong evidence that violation of hypergamy leads to a significant increase in domestic violence. Further, we provide suggestive evidence that this result arises because violation of hypergamy is likely to undermine patriarchal beliefs and norms about gender roles, and also because it is likely to increase men's likelihood of using domestic violence as an instrument. Our findings suggest that policies that seek to empower women and promote gender equality might paradoxically increase women's exposure to domestic violence.
Keywords: J12; J16; O12; O15; 330; Domestic Violence; Hypergamy; India; Partial Identification; Women